Budi Ramadan mKitchen IIUM students - Ahmad Dahlan, Abdul Rahman; Alias, Majdan; Ibrahim, Jamaludin; Ahmad H.Osman, Rahmah; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Abdul Razak, Dzuljastri; Mohd Ali, Noor Azian; Abdul Aziz, Normaziah; Mohamadali, Noor Azizah; Mahri, Nurhafizah; et al. (mKitchen KICT, 2022)
This book explains mKitchen IIUM students experience in the real journey of integrating food entrepreneurship with Budi Sejahtera. The students participated as a vendor in the Bazaar Ramadan organized by EDC IIUM. This one-month Bazaar Ramadan provides the students the real experience of food entrepreneurs. While preparing premium food for Bazaar Ramadan, the students also prepared premiums food for distribution to the asnaf.